Plasmid-Based Generation of Induced Neural Stem Cells from Adult Human Fibroblasts - Capetian, Philipp; Azmitia, Luis; Pauly, Martje G.; Krajka, Victor; Stengel, Felix; Bernhardi, Eva-Maria; Klett, Mariana; Meier, Britta; Seibler, Philip; Stanslowsky, Nancy; Moser, Andreas; Knopp, Andreas; et al. (Frontiers in Cellular Neuroscience, 2016)
Direct reprogramming from somatic to neural cell types has become an alternative to induced pluripotent stem cells. Most protocols employ viral expression systems, posing the risk of random genomic integration. Recent developments led to plasmid-based protocols, lowering this risk. However, these protocols either relied on continuous presence of a variety of small molecules or were only able to reprogram murine cells. We therefore established a reprogramming protocol based on vectors containing the Epstein-Barr virus (EBV)-derived oriP/EBNA1 as well as the defined expression factors Oct3/4, Sox2, Klf4, L-myc, Lin28, and a small hairpin directed against p53. We employed a defined neural medium in combination with the neurotrophins bFGF, EGF and FGF4 for cultivation without the addition of small molecules. After reprogramming, cells demonstrated a temporary increase in the expression of endogenous Oct3/4. We obtained induced neural stem cells (iNSC) 30 days after transfection. In contrast to previous results, plasmid vectors as well as a residual expression of reprogramming factors remained detectable in all cell lines. Cells showed a robust differentiation into neuronal (72%) and glial cells (9% astrocytes, 6% oligodendrocytes). Despite the temporary increase of pluripotency-associated Oct3/4 expression during reprogramming, we did not detect pluripotent stem cells or non-neural cells in culture (except occasional residual fibroblasts). Neurons showed electrical activity and functional glutamatergic synapses. Our results demonstrate that reprogramming adult human fibroblasts to iNSC by plasmid vectors and basic neural medium without small molecules is possible and feasible. However, a full set of pluripotency-associated transcription factors may indeed result in the acquisition of a transient (at least partial) pluripotent intermediate during reprogramming. In contrast to previous reports, the EBV-based plasmid system remained present and active inside the cells at all time points.